2022
DOI: 10.3390/ma15196620
|View full text |Cite
|
Sign up to set email alerts
|

A Tailored Preparation Method of Variable Strength for Ultra-High-Strength Steel Sheet and Mapping Mechanism between Process and Property

Abstract: The spatiotemporal phase transformation during hot stamping would considerably effect the microstructure and mechanical properties of steels. In order to manufacture hot-stamping components of ultra-high-strength steel with tailored mechanical properties, the effect of the quenching time and the temperature of the die on the phase-transformation characteristics and mechanical property of ultra-high-strength steel was deeply studied. A finite element (FE) model coupled with a thermomechanical phase was employed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…In recent years, the process parameters (such as austenitizing temperature, cooling rate, pressure magnitude, holding time and die exit temperature) in the hot forming process, which directly affect the important factors of its mechanical properties, have been studied intensively and extensively [8][9][10][11][12][13]. Quan et al [14] investigated in depth the effect of the quenching time and the temperature on the phase-transformation characteristics and mechanical property of ultra-high-strength steel. Jiang et al [15] closely examined the microstructure and mechanical properties of 22MnB5 steel during hot stamping, and found that the microstructure was uniformly distributed martensite when the austenitization temperature was 930 • C and the holding time was 4.5 min.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, the process parameters (such as austenitizing temperature, cooling rate, pressure magnitude, holding time and die exit temperature) in the hot forming process, which directly affect the important factors of its mechanical properties, have been studied intensively and extensively [8][9][10][11][12][13]. Quan et al [14] investigated in depth the effect of the quenching time and the temperature on the phase-transformation characteristics and mechanical property of ultra-high-strength steel. Jiang et al [15] closely examined the microstructure and mechanical properties of 22MnB5 steel during hot stamping, and found that the microstructure was uniformly distributed martensite when the austenitization temperature was 930 • C and the holding time was 4.5 min.…”
Section: Introductionmentioning
confidence: 99%